The Impact of Asymmetric Power Pricing on Sales Mode Choice and Channel Entry in An E-Commerce Platform Supply Chain - Liu, Bin; Wang, Ting; Rong Zhang (International Journal of Industrial Engineering: Theory, Applications and Practice, 2026)
Globally, e-commerce platforms’ private labels are becoming increasingly prevalent, posing a significant competitive threat to manufacturers’ brands. This study focuses on supply chain scenarios where manufacturers sell products to consumers through platform resale or agency models. Using Stackelberg and bargaining game models, we analyze platform decisions to enter private label markets and both parties’ preferences for sales models. Findings reveal that in the Stackelberg game, platforms favor launching private labels when costs and product substitutability are low. In the bargaining game, stronger platform bargaining power increases the likelihood of introducing private labels under the agency model. Regarding sales model selection, both parties prefer the resale model when costs are low and substitutability is high. As bargaining power increases, the range of scenarios where both parties support the resale model expands. Furthermore, the greater the market potential, the broader the regions where both parties opt for the agency model.